Massive invasion of exotic Barbus barbus and introgressive hybridization with endemic Barbus plebejus in Northern Italy: where, how and why?. Issue 21 (18th September 2013) - Meraner, A.; Venturi, A.; Ficetola, G. F.; Rossi, S.; Candiotto, A.; Gandolfi, A.
Abstract Biological invasions and introgressive hybridization are major drivers for the decline of native freshwater fish. However, the magnitude of the problem across a native species range, the mechanisms shaping introgression as well as invader's dispersal and the relative role of biological invasions in the light of multiple environmental stressors are rarely described. Here, we report extensive (N = 665) mtDNA sequence and (N = 692) microsatellite genotypic data of 32 Northern Adriatic sites aimed to unravel the invasion of the European Barbus barbus in Italy and the hybridization and decline of the endemic B. plebejus. We highlight an exceptionally fast breakthrough of B. barbus within the Po River basin, leading to widespread introgressive hybridization with the endemic B. plebejus within few generations. In contrast, adjacent drainage systems are still unaffected from B. barbus invasion. We show that barriers to migration are inefficient to halt the invasion process and that propagule pressure, and not environmental quality, is the major driver responsible for B. barbus success. Both introgressive hybridization and invader's dispersal are facilitated by ongoing fisheries management practices. Therefore, immediate changes in fisheries management (i.e. stocking and translocation measures) and a detailed conservation plan, focussed on remnant purebred B. plebejus populations, are urgently needed.